Agrochemicals Uses and Pattern in the Western Central Tableland: A Case Study - Mohanty, Aman Kumar; Sundaray, Jitendra Kumar; Das, Ipsita Iswari; Nayak, Sipra; Sahoo, Lakshman; Kumar, Rajesh (International Journal of Economic Plants, 2023)
A survey-based study was conducted during February, 2022 in the western central tableland, Sambalpur and Bargarh district of Odisha, India to understand and identify the pattern of agrochemicals usage. A total of hundred farmers from both the districts, according to the guidelines of a questionnaire survey, were interviewed, with respect to the type of crop cultivation practice, types of agrochemicals used, the investment on agrochemicals procurement annually, the effect of agrochemicals on the peripheral environment, and impact on health conditions of the farmers. From the survey conducted, it was found that the use of DuPont Pexalon (Triflumezopyrim), Acephate, 505 (Cypermethrin+Chlorpyriphos) and SAATHI (Pyrazosulfuran ethyl), were higher in Bargarh region, while the usage of Round-up (Glyphosate), Osheen (Dinotefuran) and Reagent (Phenyl pyrazole) were found to be more utilized in the Sambalpur zone for pest control. The survey also helped in identification of the aftereffects of agrochemicals on environment, which includes loss of microbial population, frogs, birds, earthworms from the agricultural fields. The survey also indicated towards the effects of agrochemicals on the farmers health as well. This study would further contribute towards investigating the impact of these agrochemicals on the aquatic life, the amount of leaching occurs, and the preventive measures, that should be taken, to lessen the use of agrochemicals (Pesticides, herbicides and insecticides), and to introduce alternate forms of agrochemicals to ensure crop safety.